Advances in Understanding Materials for Rechargeable Lithium Batteries by Atomic Force Microscopy. Issue 1 (29th April 2018) - Wang, Shuwei; Liu, Qi; Zhao, Chenglong; Lv, Fengzheng; Qin, Xianying; Du, Hongda; Kang, Feiyu; Li, Baohua
Abstract : The development of advanced lithium batteries represents a major technological challenge for the new century. Understanding the fundamental electrode degradation mechanisms is important for battery performance improvements. The complex electrochemical processes inside a working battery are being explored to a limited extent. Various advanced material characterization techniques have been used to monitor dynamic conditions for optimizing battery materials. State‐of‐the‐art atomic force microscopy methods have been applied to energy storage systems, specifically lithium‐ion batteries. Atomic force microscopy is an ideal tool to provide localized morphological, chemical, and physical information at nanoscale for the in‐depth understanding of the electrochemical processes, reaction mechanisms, and degradation of battery materials. Here, we review recent progress in the development and application of atomic force microscopy for high‐performance lithium‐ion batteries. We discuss atomic force microscopy as an analytical tool to help researchers understand graphite, silicon, layered metal oxides, and other representative electrode materials. We summarize the importance of atomic force microscopy technique in studying the next‐generation Li–S and Li–O2 batteries. We also highlight some of the remaining challenges and possible solutions for future development.